COVID 19 effect on Venezuelan migrants’ income: the Peruvian case research study - Guillen, Jorge; Arbaiza, Lydia (Kubilay özyer, 2023)
This paper shed light on analyzing the effect of the Pandemic on Venezuelan Migrants’ Income in Peru. The Covid 19 Pandemic (Coronavirus Pandemic) enforced governments to apply the “Hammer Blow” which produced recession and consequently unemployment. Governments offset the latter effect by applying some subsidies to the Poor. The subsidy was not delivered to Venezuelan Immigrants in Peru. Therefore, our study attempts to explore the effect of the Coronavirus Pandemic on the Income of Venezuelan Immigrants. The study controls for gender and discrimination. Since 2017, the economic and political situation in Venezuela triggered migration beyond their frontiers. Peru is the second country with the high migration of Venezuelans, the first is Colombia which is the neighborhood. The migration reduced the labor force in the country that receives the population but in some cases, the delinquency rates increased after the wave of Venezuelans relocated to a particular country. We consider the survey: “Encuesta Nacional de la Población Venezolana en Peru” (ENPOVE) to perform the study which was conducted during the peak of migration.
Keywords: ENPOVE; Gender inequality; ENPOVE; Venezuelan migration in Peru; Desigualdad de género; Migración venezolana en Perú; COVID 19; COVID 19; https://purl.org/pe-repo/ocde/ford#5.02.04